Development of History-Based Digital Book Based on the 19th Century Lampung’s People Army Struggle in Local History Lessons - Agus Mastrianto; Sariyatun Sariyatun; Nunuk Suryani (BIRCU, 2020)
This study aims to develop teaching materials in the form of digital ebook by integrating local historical material on the Struggle of the Lampung People's Army at the State University in Lampung Province. The method used in this research is the development research (R&D) method. The stages of this research include the stages of analysis, design, development, implementation, and evaluation. The subjects in this study consisted of two material validators, two media validators, 48 students of semester VII students, one of whom was a lecturer in history education. The results of this development research show that digital history-based teaching materials (ebooks) based on local people's struggles in Lampung are proven to be valid based on the assessment of material experts and media experts. Based on the results of small group trials, limited group trials and large group trials show that digital history-based teaching materials based on local history of the struggle of the Lampung people's army proven to be effective and in accordance with needs analysis.